Hoax and Provocative Contents by Muslim Cyber Army (MCA) and Its Enforcement in Indonesia - Wahyuni, Nungki; Nguyet, Dinh Mai (Indonesian Journal of Counter Terrorism and National Security, 2022)
The existence of globalization with marked advances in technology and communication does not only have a positive impact on society. It is undeniable that the negative impact always lurks the people who take advantage of these advances. One of the negative impacts that arise is the existence of crimes that occur in cyberspace or cyber crime or commonly known as cybercrime. Recently, Indonesia was faced with one of these forms of cybercrime, namely an organization calling itself the Muslim Cyber Army. The motives of the actions and the impacts left by the existence of the Muslim Cyber Army can be identified and studied further by looking at the laws and regulations in Indonesia and their relationship with one of the fields of legal study, namely Law and Technology.